Processing Determinism. Issue 1 (March 2015) - O'Grady, William; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> I propose that the course of development in first and second language acquisition is shaped by two types of processing pressures—internal efficiency‐related factors relevant to easing the burden on working memory and external input‐related factors such as frequency of occurrence. In an attempt to document the role of internal factors, I consider a series of case studies involving contrasts that are rarely instantiated in the input, yet show early mastery. I conclude with some general remarks about the nature of development and the possibility that it unfolds more uniformly than often suggested.